Active layer and permafrost monitoring in Livingston Island, Antarctic: first results from 2000 and 2001 - Ramos Sainz, Miguel (2019)
Two shallow boreholes were drilled in 2000 in the vicinity of the Spanish Antarctic Station Juan Carlos I in Livingston Island (South Shetlands, Antarctic – 62°39`S, 60°21`W). A borehole is located in Cerro Incinerador at 35 m ASL and was drilled to 240 cm depth in quartzite bedrock (Myers Bluff Formation). The other is located in Reina Sofia Peak at 275 m ASL and was drilled in a matrix-supported diamicton to a depth of 110 cm. PVC tubes were inserted in the drillings and thermistor chains based on miniature data loggers were installed inside them. Temperature data is collected at 4-hour intervals. The first year of data from the boreholes evidence their different setting, both in what respects to altitude and to ground thermal properties. The results from the borehole at Cerro Incinerador suggest that the active layer is very thick there and the borehole does not reach the (possible) permafrost table. At Reina Sofia Peak, the lower section of the drilling is below the permafrost table. In this paper, the ground temperature data from the two boreholes from 2000 to 2001 will be presented.